Los Sistemas de Información su Importancia y Efectos en la Toma de Decisiones de las Empresas Auditoras del Cantón Quito. - Cevallos Rubio, Juan Alejandro (2015)
Information as a necessary and indispensable resource has allowed through a modern and comprehensive data interaction process large volumes grow as time passes are capable of being stored in increasingly complex ways and small, in this way inevitably creating information systems that administer and manage all this content in an efficient manner, an increasingly digital resource that has the ability to report data integration allows for interpretation and analysis. So from this issue arises the need to develop a thesis to identify, evaluate and analyze the information systems used by audit firms canton Quito to issue an earnings report that shows the differences in the use and risks of these platforms to issue a conglomerate of conclusions and recommendations to users and to promote the improvement of the utilization of these components are increasingly needed for business development.